Bevacizumab with chemotherapy in patients with KRAS wild-type metastatic colorectal cancer: Czech registry data. (January 2015) - Kubáčková, Kateřina; Bortlíček, Zbyněk; Pikus, Tomáš; Linke, Zdeněk; Pokorná, Petra; Vyzula, Rostislav; Prausová, Jana
ABSTRACT : Aim : This retrospective analysis investigated the effectiveness of combination therapy with bevacizumab and chemotherapy in the first-line treatment of patients with KRAS wild-type metastatic colorectal cancer.Patients & methods : Patients with KRAS wild-type metastatic colorectal cancer in the CORECT registry who initiated treatment with bevacizumab between 2008 and 2012 were enrolled. Overall survival and progression-free survival were the main effectiveness end points.Results : A total of 981 patients were enrolled. Median progression-free survival was 11.3 months (95% CI: 10.7–11.8) and median overall survival was 28.4 months (95% CI: 26.2–30.6). The most common adverse events were thromboembolic disease (4%) and hypertension (3.5%).Conclusion: This retrospective analysis shows the effectiveness of bevacizumab with chemotherapy in patients with KRAS wild-type metastatic colorectal cancer.